The Postcolonial Gramsci - Srivastava, Neelam; Bhattacharya, Baidik (Routledge Research in Postcolonial Literatures, 2012)
The importance of Antonio Gramsci's work for postcolonial studies can hardly be exaggerated, and in this volume, contributors situate Gramsci's work in the vast and complex oeuvre of postcolonial studies. Specifically, this book endeavors to reassess the impact on postcolonial studies of the central role assigned by Gramsci to culture and literature in the formation of a truly revolutionary idea of the national-a notion that has profoundly shaped the thinking of both Frantz Fanon and Edward Said. Gramsci, as Iain Chambers has argued, has been instrumental in helping scholars rethink their understanding of historical, political, and cultural struggle by substituting the relationship between tradition and modernity with that of subaltern versus hegemonic parts of the world. Combining theoretical reflections and re-interpretations of Gramsci, the scholars in this collection present comparative geo-cultural perspectives on the meaning of the subaltern, passive revolution, hegemony, and the concept of national-popular culture in order to chart out a political map of the postcolonial through the central focus on Gramsci.